Advances in Hemodiafiltration - Karkar, Ayman; Karkar, Ayman (IntechOpen, 2016)
Hemodiafiltration (HDF) is an advanced renal replacement therapy that can reduce morbidity and mortality and improve the quality of life of dialysis patients. This special edition of the Advances in Hemodiafiltration book is empowered with several well-established and experienced authors, who have written clear and informative chapters. The book covers basic physiologic principles of HDF and its requirements, implementation, and achievement of best possible clinical outcomes and includes results of published randomized controlled clinical trials. Advances in Hemodiafiltration can be considered as a practical guide to daily practice and a reference for medical and nursing staff involved in taking care of dialysis patients.
English
Keywords: Ophthalmology; Renal medicine & nephrology